SIMULASI OPTIMASI SISTEM PLTH MENGGUNAKAN SOFTWARE HOMER UNTUK MENGHEMAT PEMAKAIAN BBM DI PULAU PENYENGAT TANJUNG PINANG KEPULAUAN RIAU - Maula Sukmawidjaja; Ilham Akbar (Website, 2013)
Abstract Currently electrification on Penyengat Island supplied by Diesel Power Plants with total capacity 285 kW to serve peak load system about 250 kW. This research aims to improve the efficiency of Fuel consumption, by means of implementing a Hybrid Power Plants on Penyengat Island. Methods used in this research is simulating and analyzing the result of optimation Hybrid Power Plants system by using Homer Software version 2.81. This software to optimize based on the lowest value of the NPC (Net Present Cost). In this research, result of the simulation and optimation by Homer Software, show that the Hybrid power plant’s most optimal to be applied on the Penyengat Island is integration between PLTB, PLTS & PLTD. In this condition, the contribution of the electricity production system of PLTS at 43%, PLTB at 41%, PLTD at 16%. With capital cost for 1.058.906, Operating Cost for 268.758 per year, Net Present Cost for 3.938.507, and Cost of energy for 0.249/kWh. While PLTH fuel consumption is 205.601 litres/year, saving fuel consumption of 316.499 litres/year or 60,6%/year. And saving fuel consumption cost of 265.859/year Keywords: Penyengat Island, PLTH, PLTS, PLTD, PLTS, Homer